Knowledge, Attitude And Practice Towards Halal Cosmetics In Malaysia - Siahooei, Ali Ameri (2011)
This research attempts to know about the relationship and correlation between the Muslims level of Knowledge and Attitude and Practice towards the cosmetics which currently some producers found to produce in Halal way. The researcher is going to apply KAP Model by Maloney 1975 to find out the relationship between its variables Knowledge, Attitude and Practice (behavior) towards Halal cosmetics as youngest Halal product base on Muslims demand for various product but on permitted way by Islamic Law (Shari\'a).